Association between serum ferritin and the severity of drug eruptions. Issue 2 (25th September 2019) - Pan, Yunlei; Tang, Shunli; Zheng, Siting; Li, Sheng; Zhu, Dingxian; Fang, Hong; Qiao, Jianjun
Abstract: Background: Early recognition and treatment for severe drug eruption are important in improving clinical outcomes. A few studies have reported laboratory parameters to evaluate the severity of drug eruptions. This study aimed to determine the association between serum ferritin and the severity of drug eruptions. Methods: We retrospectively reviewed patients diagnosed with drug eruptions in our hospital from 2013 to 2018. Results: We identified 85 patients (mean age 53.4 years), 20 in the severe cutaneous adverse drug reactions (SCADRs) group and 65 in the non‐SCADRs group. Serum ferritin level was higher in the SCADRs group compared with that in the CADRs group ( P <.001). Serum ferritin was positively associated with peripheral white blood cell count, aspartate aminotransferase level, alanine aminotransferase level, blood glucose level, blood creatinine level, and body temperature. Receiver operating characteristic (ROC) analysis revealed a good diagnostic value of ferritin (area under the curve [AUC]:0.87, 95% confidence interval [CI]:0.78‐0.96) with a sensitivity of 80% and a specificity of 87.7% at a cutoff value of 416.15 ng/mL. Conclusions: Serum ferritin is significantly associated with the severity of CADRs and hence might be potentially used to evaluate the severity of CADRs.